Voting behaviour in Indonesian democracy : a study of Sambas regency election 2006 - Rofi, Fahrur (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2010)
Election as a form of direct political participation is considered as the chance to participate in determining the political outcome. Through election, all people of the region exercised their rights in choosing their representatives in a governmental body that is expected to actualise their aspirations and solve their problems. This study aims to investigate the voting behaviour of the Melayu, Dayak and Chinese ethnic groups in 2006 Sambas regency election in Indonesia. The candidates who contested in the Sambas Regency election in 2006 were all from the Melayu ethnic group. The absence of other ethnic groups in the candidacy for the election raises questions such as how was the participation of other ethnic groups in the election, and how the candidates represented the interests of other ethnic groups in the region. In order to study the general tendency of the voting behaviour in the Sambas regency election, this research is conducted using the quantitative approach. A survey method was used to collect data using a set of questionnaire related to the research question that was given to 270 respondents. Apart from the primary data, a host of secondary data was collected from the Sambas Regency Election Commission and from the Sambas Regency government. The results of this research shows that firstly, in a local election, the society or the voters play an important factor in determining the winning of a particular candidate. Secondly, there are various factors that function as the main considerations for the voters or the society in choosing a candidate. The factors are ethnic affiliation, social economic status and social location. Thirdly, there is correlation between independent variable toward dependent variable. Fourth is the total percentage of the correlation between the independent variables (ethnic affiliation, social economic status and social location) toward dependent variable (candidate orientation) is 9.80%. The fifth point is the ethnic affiliation does not have a significant correlation toward candidate orientation in the Sambas regency election 2006. The Sixth point is that the social economic status has a significant correlation toward candidate orientation in the Sambas regency election 2006.